Delimitation of Some Taxa of Ulnaria and Fragilaria (Bacillariophyceae) Based on Genetic, Morphological Data and Mating Compatibility - Yulia Zakharova; Artyom Marchenkov; Darya Petrova; Yurij Bukin; Aleksey Morozov; Yekaterina Bedoshvili; Yulia Podunay; Olga Davidovich; Nikolai Davidovich; Alexander Bondar; Maria Kahlert; Yelena Likhoshway (Diversity, 2023)
Fragilaria and Ulnaria are two closely related diatom genera for which the delimitation and circumscription of several species is unclear. We studied strains isolated from Lake Baikal and compared them with the species from freshwater reservoirs in Europe and Asia using phylogenetic and species delimitation methods, microscopy and interclonal crossing experiments. The results of the phylogenetic analyses of the fragments of rbcL and 18S rRNA genes revealed that baikalian F. radians clade was independent from the representatives of the genus from other localities. Among Ulnaria we found the following 18S rRNA phylogenetic tree groups at species level: U. acus, U. ulna and U. danica. Genetic distance between genera varied between 3.9–10.2% substitutions in rbcL gene and 3.2–11.5% in 18S rRNA. The boundary between intraspecies and interspecies polymorphism for studied species of Ulnaria and Fragilaria in these marker genes was around 0.8% substitutions. Morphometric characters of individual strains showed their variability and division into F. radians, U. acus and U. ulna together with U. danica. Strains of U. acus and U. danica from different localities of Europe and Asia were sexually compatible inside the species. Sexual reproduction has never been observed in monoclonal cultures, either between this species or with strains of the Fragilaria.